Integrasi Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Literasi Anak Sekolah Dasar - Fakhridana, Farhan Muzakki; Azizah, Siti Nur; Annisa, Annisa; Zaironi, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the integration of artificial intelligence in Islamic Education to improve elementary students' literacy. It is a library research with a quantitative descriptive approach, utilizing SINTA-accredited literature from 2021-2025 and international publications. The analysis involved identification, data selection, data extraction, and content analysis to map the relationship between AI, TPACK, basic literacy, and Islamic educational values. The findings indicate that AI has the potential to enhance literacy through adaptive, interactive, and contextual learning, but its implementation must be carefully guided. The study also shows that AI can strengthen literacy while promoting the values of manners and character, ensuring technology serves not just as a cognitive tool. An AI-Literacy model of Islamic Integration is proposed, combining AIEd, TPACK, literacy, and the principle of at-ta'dīb as the foundation for AI integration in PAI. This model offers a conceptual framework for PAI teachers to design ethical and relevant literacy learning in primary schools.